New and Pre-existing Eating Disorders Among Adolescents and Young Adults During the COVID-19 Pandemic: A Population-Based Cohort Study - Amreen Babujee; Hong Lu; Therese Stukel; Natasha Saunders; Astrid Guttmann; Paul Kurdyak; Simone Vigod; Longdi Fu; Alene Toulany (International Journal of Population Data Science, 2024)
Objectives Our understanding of the contribution of new presentations versus pre-existing eating disorders during the COVID-19 pandemic is limited. This study aims to evaluate rates of emergency department (ED) visits and hospitalizations for eating disorders among adolescents and young adults (YA) new to care and those with pre-existing eating disorders during the pandemic.